A 1064 nm single-photon lidar for three-dimensional imaging. Issue 1 (July 2021) - Guo, Jingjing; Fei, Xiaoyan; Ge, Peng; Li, Zhengqi; Lv, Yang; Sheng, Lei
Abstract: Single-photon light detection and ranging system has been widely used in three-dimensional (3D) imaging for its advantages in weak echo detection and high resolution. However, long-range imaging is a great challenge due to the device performance limits and strong solar irradiance. In this paper, we experimentally demonstrate a single-photon imaging system with an operation wavelength of 1064 nm in daytime. An all-fiber optical system with a two-dimensional rotation platform is designed to realize a wide scanning. And a sub-pixel scanning method is used to improve spatial resolution. Image reconstruction is based on the iterative shrinkage-threshold algorithm; herein the noise threshold is self-adaptive to the received photon-counting distribution. Multi-range information can be retrieved from each pixel and 3D point cloud is finally generated. Results show that the range resolution is 38 cm and the spatial resolution is about 7.4 cm at the distance of 2.13km, three times of the diffraction limit of the optical system.